Mercury levels in fly ash and APC residue from municipal solid waste incineration before and after electrodialytic remediation - Dias-Ferreira, C (2017)
Fly ash (FA) and Air Pollution Control (APC) residues collected from three municipal solid waste incinerators (MSWI) in Denmark and Greenland were treated by electrodialytic remediation at pilot scale for 8 to 10 h. The original residues and the treated material were analysed for mercury (Hg) in order to assess the influence of the electrodialytic treatment on the concentrations of this element. Mercury levels varied with the MSWI residue, ranging from 0.41 mg kg1 in FA sample from electrostatic precipitator (ESP) to 8.38 mg kg1 in MSWI residues from a semi-dry system with lime and activated carbon. Two distinct behaviours were observed for mercury as a result of the electrodialytic treatment. This element became enriched in the MSWI residues from the semi-dry system with activated carbon, whereas it decreased in ESP's and cyclone's FA. This work presents for the first time information about the effect of electrodialytic treatment on mercury levels and discusses the valorisation options for these MSWI residues. © 2016 WIT Press.